Alliance performance and subsequent make‐or‐ally choices: Evidence from the aircraft manufacturing industry - Ren, Charlotte R.; Mulotte, Louis; Dussauge, Pierre; Anand, Jaideep (Strategic Management Journal, 2022)
Abstract Research Summary We examine how the performance of a firm's prior alliances influences its propensity to persist with the alliance mode or switch to independent operations in the context of new product introductions (NPIs). Drawing on the behavioral theory of the firm (BTOF), we argue that a firm's alliance performance has a U‐shaped effect on its likelihood of undertaking the subsequent NPI independently and that competitive intensity strengthens this U‐shaped relationship. We also predict that firms with above‐aspiration alliance performance are more likely to achieve breakthrough performance in the subsequent NPI if they switch to independence than if they continue to ally. Data on NPIs in the global aircraft manufacturing industry (1944–2000) support our hypotheses. Our study extends the alliance literature and contributes to research on how firm performance influences subsequent strategic choices. Managerial Summary The dilemma of whether to continue or exit an alliance or relationship is a common one for individuals, countries, and firms. Our study examines firms' strategic decision to switch to independent operations after having partnered with other firms. Using the aircraft product development context, we show that firms that make such a change in their strategy are the ones that performed either much better or much worse than what they expected. Firms with alliance performance close to their expectations tend to persist with their current strategy. Of the firms that change their strategy, the high performers benefit much more from changing their strategy than low performers. We provide insights regarding when it is preferable for managers to continue to ally or to switch to independence, especially in launching new products.